Instructional Strategies and Their Impact on Efl Students’ Reading Comprehension: An Empirical Study at Champasack University - Vongsawath, Khanngeun; Fauziati, Endang; Hikmat, Mauly Halwat (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to examine how certain teaching methods to improve reading comprehension skills of EFL students at the Faculty of Education Champasack University. However, empirical evidence on the impact of instructional reading strategies on EFL students’ reading comprehension and learner perceptions in Lao university contexts remains limited. The use of specific selection of teaching methods, such as explicit strategy instruction and collaborative reading activities, creates the command of students to use strategies at different levels of reading comprehension. The study involved 25 final-year EFL students and 5 lecturers who were purposefully sampled. The data were collected using the following methods and instruments: open-ended questionnaires, semi-structured interviews, pre-test and post-tests, classroom observations, and reading comprehension tests. The qualitative component of the study involved thematic analysis of the participants’ perceptions and classroom interactions, which provided triangulation for the study. The analysis of the data indicated that the reading comprehension instructional strategies had the most impact on the students’ ability to comprehend text at the literal and inferential levels, i.e. identifying the main ideas, supporting details, and making simple inferences. There was limited improvement in the students’ critical reading and advanced strategic behaviors, which demonstrated the need for extended and continued training to improve comprehension at the higher levels. The most important findings of the study also demonstrated the positive impact that structured and strategy-based instruction (SBI) has on EFL students’ reading comprehension. This research contributes important implications for EFL teaching in higher education which indicated the need for constant integration of strategy-focused and student-centered reading instruction.  AbstrakTujuan dari penelitian ini adalah untuk mengkaji bagaimana metode pengajaran tertentu dapat meningkatkan keterampilan pemahaman membaca mahasiswa EFL di Fakultas Pendidikan Universitas Champasack. Namun, bukti empiris mengenai dampak strategi pembelajaran membaca terhadap pemahaman membaca dan persepsi pembelajar EFL di konteks perguruan tinggi di Laos masih terbatas. Penggunaan bagian tertentu dari metode pengajaran, seperti instruksi strategi eksplisit dan kegiatan membaca kolaboratif, menciptakan kemampuan mahasiswa untuk menggunakan strategi pada berbagai tingkat pemahaman membaca. Penelitian ini melibatkan 25 mahasiswa EFL tahun akhir dan 5 dosen yang dipilih secara purposif. Data dikumpulkan dengan menggunakan metode dan instrumen berikut: kuesioner terbuka, wawancara semi-terstruktur, pre-test dan post-test, observasi kelas, serta tes pemahaman membaca. Komponen kualitatif dari penelitian ini melibatkan analisis tematik terhadap persepsi peserta dan interaksi kelas, yang memberikan triangulasi untuk penelitian ini. Analisis data menunjukkan bahwa strategi pengajaran pemahaman membaca memiliki dampak terbesar pada kemampuan mahasiswa untuk memahami teks pada tingkat literal dan inferensial, yaitu mengidentifikasi ide pokok, rincian pendukung, dan membuat inferensi sederhana. Ada peningkatan terbatas dalam kemampuan membaca kritis dan perilaku strategis lanjutan mahasiswa, yang menunjukkan perlunya pelatihan yang lebih panjang dan berkelanjutan untuk meningkatkan pemahaman pada tingkat yang lebih tinggi. Temuan paling penting dari penelitian ini juga menunjukkan dampak positif dari pengajaran terstruktur dan berbasis strategi (SBI) terhadap pemahaman membaca mahasiswa EFL. Penelitian ini memberikan implikasi penting bagi pengajaran EFL di pendidikan tinggi yang menunjukkan perlunya integrasi berkelanjutan dari pengajaran membaca yang berfokus pada strategi dan berpusat pada siswa.